2021
DOI: 10.20944/preprints202104.0236.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hesitancy of Arab Healthcare Workers Towards COVID-19 Vaccination: A Large-Scale Multinational Study

Abstract: Background: Health Care Workers (HCWs) are at increased risk of acquiring and transmitting COVID-19 infection. Also, they present role models for communities with regards to attitudes towards COVID-19 vaccination. Hence, hesitancy of HCWs towards vaccination can crucially affect the efforts aiming to contain the pandemic. Previously published studies paid little attention to HCWs in Arab countries, which has a population of over 440 million. Objectives: to assess the rates of COVID-19 vaccine hesitancy in Arab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
2
9
0
1
Order By: Relevance
“…The current study reported increased acceptance of COVID-19 vaccine among males (55.0%, OR=3.594) that is in line with the previously reported findings. 25,28 The present study determined absence of apprehensions as major determinant of vaccine acceptance (OR=5.745, 95% CI, 2.826-11.628, p <0.001), that is in agreement with the past evidence. 29,30 Determinants of increased apprehension about the COVID-19 vaccine concluded following reasons, "Mistrust on the government approved vaccine" (36.5%) followed by the low confidence on the "authenticity and efficacy of the available vaccine" (34.5%) and serious adverse effects of the vaccine (29.4%).…”
Section: Discussionsupporting
confidence: 91%
“…The current study reported increased acceptance of COVID-19 vaccine among males (55.0%, OR=3.594) that is in line with the previously reported findings. 25,28 The present study determined absence of apprehensions as major determinant of vaccine acceptance (OR=5.745, 95% CI, 2.826-11.628, p <0.001), that is in agreement with the past evidence. 29,30 Determinants of increased apprehension about the COVID-19 vaccine concluded following reasons, "Mistrust on the government approved vaccine" (36.5%) followed by the low confidence on the "authenticity and efficacy of the available vaccine" (34.5%) and serious adverse effects of the vaccine (29.4%).…”
Section: Discussionsupporting
confidence: 91%
“… Unforeseen effects of the vaccine, female sex, urban residence, university/post-graduate, married respondents, absence of a history of allergy to food or drugs, younger age, those never had the flu vaccine. N/A N/A 36 Yuval Palgi 36 , 62 Israel 254 60.04 ± 15.44, range 24-100 40.6% N/A N/A N/A N/A N/A depression and peritraumatic stress (ORs >2), anxiety (OR > 3) N/A N/A 37 Ameerah M N Qattan 59 , 63 Saudi Arabia 673 18-60< 67.06% 79.4% Chronic condition 71.32% N/A 50.52% N/A N/A Male healthcare worker N/A 38 Qunaibi, E. 60 , 64 21 Arabcountries 5708 30.6 ± 10 55.6% 14% Chronic diseases 5.6% 67.9% bachelor’s degree or higher Rate of vaccine hesitancy among Arabic-speaking HCWs 25.8% The western regions of the Arab world (Egypt, Morocco, Tunisia, and Algeria) had the highest rates of hesitancy Concerns about side effects and distrust of the expedited vaccine production and healthcare policies. Age of 30–59, previous or current suspected or confirmed COVID-19, female gender, not knowing the vaccine type authorized in the participant’s country, and not regularly receiving the influenza vaccine.…”
Section: Methodsmentioning
confidence: 99%
“… 67.9% of students believed that the way to overcome the COVID‐19 pandemic is mass vaccination (56.5%), adverse effects of the vaccine (96.8%), its ineffectiveness (93.2%) and enough testing (80.2%), safety (54.0%), acquisition of COVID-19 from the vaccine itself 63.3% Insufficient information regarding vaccine 72.8%, its adverse effects (potential 74.2% Unknown 56.3%, financial cost 68%, insufficient trust in the vaccination source 55%. N/A Most students were not against vaccination (95.1%) 42 Sallam, M. 26 , 64 Arab-speaking countries 3414 31 32.7% 34.6% 30.9% 75% undergraduate study level 29.4% inject microchips into recipients 27.7%/that the vaccines are related to infertility 23.4% Females, lower educational levels, and respondents rely on social media platforms as the main source of information. N/A A reliance on social media as the main source of information about COVID-19 vaccines was associated with vaccine hesitancy.…”
Section: Methodsmentioning
confidence: 99%
“…People who are unsure whether the side effects of the COVID-19 vaccine are tolerable or not are very reluctant to take this vaccine. 79,80 Therefore, the provision of clear and scientifically valid information about the safety of the COVID-19 vaccine and its adverse outcomes should be a priority task for public health authorities. Since willingness to take the COVID-19 vaccine and its perceived safety and Risk Management and Healthcare Policy 2022:15 https://doi.org/10.2147/RMHP.S368057 DovePress 1441 efficacy are strongly linked, it is important to build confidence in the vaccine.…”
Section: Dovepressmentioning
confidence: 99%